MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN BAHASA INGGRIS MELALUI METODE SQ4R - Herlina Herlina (Jurnal Ilmiah Visi, 2016)
This research aims at obtaining data on improving English reading comprehension skill in Grade III, Labschool Primary School, Setiabudi, South Jakarta. The research subjects were the students of Grade III in the second semester of 2014/2015 school academic year. The research model used Kemmis and Mc. Taggard model covering planning, implementation, observation, and reflection. The data of reading comprehension evaluation showed that in the first cycle 55.5 % of the students gained >75 and in the second cycle 83.33 % of them gained >75. While based on the monitoring data, the activities of the teacher and the students were 55 % in the first meeting of the cycle I and increased to 85 % in the first meeting of the cycle II. Therefore, SQ4R method can improve English reading comprehension skill of the Grade III students in Labschool Primary School, Setiabudi, South Jakarta.